LTC for seniors: an intelligent gaming solution. (2016) - Maggiorini, Dario; Ripamonti, Laura Anna
The current demographic ageing in Europe is the result of a relevant economic, social, and medical development. Nevertheless, at the same time, it is also leading to a significant increase in the demand for long-term care (LTC) to seniors. One viable way to offer qualified cares at home, while at the same time containing costs, is to exploit digital technologies as enablers of a constant interaction between seniors and assisting personnel. In this paper, we propose a top-to-bottom solution to provide at home LTC to seniors: from requirements analysis, to design methodology for ambient intelligence (AmI), to a working prototypal architecture with implementation. The proposed system aims to integrate and leverage off-the-shelf technology with a particular focus on devices designed for videogame consoles. These devices, thanks to a user-friendly interface and a smooth learning curve can play a central role in minimising the interference in the senior's private life.